2006
DOI: 10.1130/b25715.1
|View full text |Cite
|
Sign up to set email alerts
|

Sevier orogenesis and nonmarine basin filling: Implications of new stratigraphic correlations of Lower Cretaceous strata throughout Wyoming, USA

Abstract: Lower Cretaceous nonmarine rocks throughout Wyoming have been used to date movements on major thrusts during the Sevier orogeny, evaluate the sedimentary response in the adjacent foreland basin, reconstruct subsidence histories, evaluate the driving mechanisms of that subsidence, and have been applied to basin modeling studies. However, detailed correlation and dating of these strata have been problematic for a century, making most detailed interpretations equivocal. New age data and correlations presented her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 37 publications
1
42
1
Order By: Relevance
“…3). This age range is supported by zircon ages, palynology, and magnetostratigraphy (May et al, 1995;Chen and Lubin, 1997;Zaleha, 2006). Furthermore, this age designation is consistent with a new age of 108.5 ± 0.2 Ma from the Himes Member of the Cloverly Formation in the Bighorn Basin (Burton et al, 2006).…”
Section: Geological Settingsupporting
confidence: 65%
See 2 more Smart Citations
“…3). This age range is supported by zircon ages, palynology, and magnetostratigraphy (May et al, 1995;Chen and Lubin, 1997;Zaleha, 2006). Furthermore, this age designation is consistent with a new age of 108.5 ± 0.2 Ma from the Himes Member of the Cloverly Formation in the Bighorn Basin (Burton et al, 2006).…”
Section: Geological Settingsupporting
confidence: 65%
“…Conglomerates of the Cloverly Formation extend up to 1000 km eastward from the Sevier fold-and-thrust belt in western Wyoming. Provenance studies of Cloverly sandstones and conglomerates indicate that they were sourced from lower Mesozoic and Paleozoic rocks exposed by Late Jurassic to Early Cretaceous thrusting in western Wyoming and central Utah (Mirsky, 1962;Furer, 1970;DeCelles and Burden, 1992;May et al, 1995;Zaleha, 2006). The provenance and distribution of coarse-grained sediments in this continental foreland basin is consistent with northeast paleoflow of Cloverly rivers (May, 1992;O'Malley, 1994;Way et al, 1994;May et al, 1995;Zaleha et al, 2001).…”
Section: Geological Settingmentioning
confidence: 55%
See 1 more Smart Citation
“…The age of the Cloverly Formation is not well-constrained, but several studies regarding Ostrom's (1970) units V-VII have found an Aptian-Albian age for those sediments with dates that range from about 113-108 Ma (Burton et al, 2006;Zaleha, 2006;Farke et al, 2014). However, D'Emic and Britt (2012) found a much younger age of about 103 Ma for sediments corresponding to unit VI or VII of Ostrom (1970) (Farke et al, 2014).…”
Section: Aptian Dinosaur Faunas Because the Arundelmentioning
confidence: 99%
“…Once work was completed, the (Darton, 1901;Rubey, 1931; Waage, 120 1959;Post and Bell, 1961). The Lakota Formation is interpreted to be temporally equivalent to 121 portions of both the Cloverly Formation of Wyoming and Montana, and the Cedar Mountain 122 Formation of eastern Utah (Way et al, 1998;Zaleha, 2006;Sames et al, 2010; Martin-Closas et 123 al., 2013;Cifelli et al, 2014). (Sohn, 1958;1979;Anderson, 1973;Cook and Bally, 1975 170 et al, 2014).…”
mentioning
confidence: 99%